2020
DOI: 10.1038/s41598-020-77380-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to TNF reprograms cell signaling pathways in fibroblast-like synoviocytes by establishing long-term inflammatory memory

Abstract: Fibroblast-like synoviocytes (FLS) play a critical role in the pathogenesis of rheumatoid arthritis (RA). Chronic inflammation induces transcriptomic and epigenetic modifications that imparts a persistent catabolic phenotype to the FLS, despite their dissociation from the inflammatory environment. We analyzed high throughput gene expression and chromatin accessibility data from human and mouse FLS from our and other studies available on public repositories, with the goal of identifying the persistently reprogr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Among the various signaling pathways that drive FLS transformation, NF-kappaB (NF-kB) signaling downstream of Tumor necrosis factor (TNF)-alpha plays a critical role in joint degeneration by driving a wide range of cellular and molecular changes leading to synovial hyperplasia, cartilage degeneration and bone loss (3,4). Importantly, the genomic and transcriptomic responses of the FLS from TNF-driven arthritis mouse model are largely comparable to the responses FLS from human RA patients (5,6). RELA/p65 is the transcription factor that mediates gene expression changes induced by the canonical NF-kB signaling pathway (7).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various signaling pathways that drive FLS transformation, NF-kappaB (NF-kB) signaling downstream of Tumor necrosis factor (TNF)-alpha plays a critical role in joint degeneration by driving a wide range of cellular and molecular changes leading to synovial hyperplasia, cartilage degeneration and bone loss (3,4). Importantly, the genomic and transcriptomic responses of the FLS from TNF-driven arthritis mouse model are largely comparable to the responses FLS from human RA patients (5,6). RELA/p65 is the transcription factor that mediates gene expression changes induced by the canonical NF-kB signaling pathway (7).…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that the sustained activated genes are NF‐kappaB, STAT and AP‐1 signalling cascades. The sustained repressed genes included critical mediators and targets of the bone morphogenetic protein (BMP) signalling pathway 94 …”
Section: Trained Immunity Discovery and Its Role In Non‐immune Skin C...mentioning
confidence: 99%
“…In addition to pathogens and other exogenous immunogenic compounds, recent research has shown that TI can also be induced indirectly through the production of specific cytokines. 94,95 Tumour necrosis factor alpha (TNFα) therapy results in longterm transcriptomic and epigenetic reprogramming in fibroblast-like synoviocytes that contribute to chronic inflammation in rheumatoid arthritis. The authors observed that the sustained activated genes are NF-kappaB, STAT and AP-1 signalling cascades.…”
Section: Trained Immunity and Its Contribution To Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, T cell chemokines can stimulate FLS activation, maintain the inflammatory phenotype of the cells, and use FLSs as antigenpresenting cells, leading to T cell activation and proliferation that act synergistically with the abnormal immune system to further drive inflammation (30,31). However, the persistent inflammatory secretion of FLSs disappears upon removal of these cellular stimuli, while some of the cell surface biomarkers remain activated in the legacy (32,33). Persistently high expression of surface proteins has a memorability, which makes FLSs more sensitive to inflammatory stimuli.…”
Section: Activation By Immune and Inflammatory Responsementioning
confidence: 99%